Peningkatan Strategi Pemasaran Rumah Kacang Melalui ChatGPT dan Kalender Konten di Kota Makassar, Provinsi Sulawesi Selatan - alvin, elza (LPPM Stikosa - AWS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are in great need of effective marketing strategies to ensure that the MSME brand is widely recognized. One of the approaches is through marketing on social media and content creation using artificial intelligence for the development of a content calendar. The main focus of this research is the enhancement of marketing strategies through the application of branding concepts and the integration of Artificial Intelligence (AI) technology. This community engagement initiative aims to provide training on the use of Artificial Intelligence (AI), specifically ChatGPT, for the creation of a content calendar and the optimization of promotions on social media. In addition to training, MSMEs are included in an Expo event held at Ciputra University. Research findings indicate that the implementation of branding strategies provides a strong identity for the MSME